Konsep Ilmu dalam Islam - Achmad Reza Hutama al-Faruqi (Universitas Darussalam Gontor, 2015)
Concept of science in Islam has its own universal dimension, metaphysic and empiric, and diffenrent from sciences came from Western worldview which limited in empiric dimension. It will be in the case that the concept of science in Islam is one of integral part of Islamic worldview; so that it has its own characteristics differed from another concept of science in other civilizations. Science according to Islamic worldview is not only cover substance of knowledge, but becomes important element in civilization as well. Related to the important of position of science, number of scholar such as Ibnu Khaldun, Imam al Ghazali, or Syed Muhammad Naquib al-Attas gave several features of science to know which one has higher priority, to be associated with how the concept of science in Islam decided later. From the discussion offered by the scholars, it will be understood that science in Islam not only encompasses theology and law, but also there is a row of other sciences such as physics, biology, and so forth need to be studied. The acquisition method of each branch of sciences have their own approach, both of internal and external sense, khabar sa>diq, and the third is intellect. A Muslim should solidly hold the Islamic tradition and not too impressed with the tradition of Western scholarly even it looks more attractive.